If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 6 = 15x + 6 Reorder the terms: 6 + 15x = 15x + 6 Reorder the terms: 6 + 15x = 6 + 15x Add '-6' to each side of the equation. 6 + -6 + 15x = 6 + -6 + 15x Combine like terms: 6 + -6 = 0 0 + 15x = 6 + -6 + 15x 15x = 6 + -6 + 15x Combine like terms: 6 + -6 = 0 15x = 0 + 15x 15x = 15x Add '-15x' to each side of the equation. 15x + -15x = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| y+x=zx | | 13=9x-4 | | 5+12x=3+18x | | ln(x)+ln(x^2-8)=ln(8x) | | 7x-15+8-15=180 | | 8(1+4b)+8b=128 | | 20y-15y=20 | | -8x-18=-12x+34 | | 3x/2+7x-7=3(2x+1) | | 2a+2a=2a | | 17-(3m+7)=2+3m-16 | | 3(4z+8)-36= | | -8-18=-12+34 | | -20D-3+3D=11D+5-8 | | 80.5=7(m+3.6) | | 5+44x=53+8x | | 7=9x-7 | | 7z-7=5+32 | | b=4b | | 34.95(5)+x(.49)=200 | | 6+7x=-8 | | 3(x-6)=2 | | -11-5(t-3)= | | y=(x^2+1)(12x)-(6x^2+7)(2x) | | 44-5x=53-8x | | 7(x-2)+2=-12 | | .10x+.35(50)=23.5 | | 4y+6=8y+2 | | 13x-203=6x-7 | | 5+2t-2=6t+9-2t | | 10.4+3.2f=5f+4 | | 4x-6=4(x+1) |